Protective effect of antioxidants contained in milk-based fruit beverages against sterol oxidation products. (March 2017) - López-García, Gabriel; Cilla, Antonio; Barberá, Reyes; Alegría, Amparo
Highlights: SOPs present in bioaccessible fractions (BFs) of functional beverages were not cytotoxic. COPs at dietary concentrations (30–60 μM) induced cell death in differentiated Caco-2 cells. Co-incubation of BFs and COPs afforded protection against cell death. Abstract: Sterol oxidation products (SOPs) have shown cytotoxic effect in human intestinal cells; however, their effect within a food matrix has not been assayed yet. This study evaluated the possible cytotoxic effect of SOPs within bioaccessible fractions (BFs) of two milk-based fruit beverages with (BFA)/without (BFB) plant sterols in differentiated Caco-2 cells and if the BFs counteracted the cytotoxic effect induced by COPs mixture (30 and 60 μM). BFs did not evoke cytotoxic effect in any of the tests carried out and they protected against the loss of intestinal cohesion, mitochondrial depolarization and necrosis induced by COPs mixture. Moreover, BFB sample protected from cell cycle arrest, lessened lysosomal injury and overproduction of ROS at 30 μM. Therefore, the formation of SOPs within milk-based fruit beverages with/without plant sterols does not contribute to intestinal epithelium damage and these types of food matrices confer additional protection against COPs at dietary concentrations.